AT 101 induces early mitochondrial dysfunction and HMOX1 (heme oxygenase 1) to trigger mitophagic cell death in glioma cells. Issue 10 (3rd October 2018) - Meyer, Nina; Zielke, Svenja; Michaelis, Jonas B.; Linder, Benedikt; Warnsmann, Verena; Rakel, Stefanie; Osiewacz, Heinz. D.; Fulda, Simone; Mittelbronn, Michel; Münch, Christian; Behrends, Christian; Kögel, Donat
ABSTRACT: In most cases, macroautophagy/autophagy serves to alleviate cellular stress and acts in a pro-survival manner. However, the effects of autophagy are highly contextual, and autophagic cell death (ACD) is emerging as an alternative paradigm of (stress- and drug-induced) cell demise. AT 101 ([-]-gossypol), a natural compound from cotton seeds, induces ACD in glioma cells as confirmed here by CRISPR/Cas9 knockout of ATG5 that partially, but significantly rescued cell survival following AT 101 treatment. Global proteomic analysis of AT 101-treated U87MG and U343 glioma cells revealed a robust decrease in mitochondrial protein clusters, whereas HMOX1 (heme oxygenase 1) was strongly upregulated. AT 101 rapidly triggered mitochondrial membrane depolarization, engulfment of mitochondria within autophagosomes and a significant reduction of mitochondrial mass and proteins that did not depend on the presence of BAX and BAK1. Conversely, AT 101-induced reduction of mitochondrial mass could be reversed by inhibiting autophagy with wortmannin, bafilomycin A1 and chloroquine. Silencing of HMOX1 and the mitophagy receptors BNIP3 (BCL2 interacting protein 3) and BNIP3L (BCL2 interacting protein 3 like) significantly attenuated AT 101-dependent mitophagy and cell death. Collectively, these data suggest that early mitochondrial dysfunction and HMOX1 overactivation synergize to trigger lethal mitophagy, which contributes to the cell killing effects of AT 101 in glioma cells. Abbreviations : ACD, autophagic cell death; ACN, acetonitrile; AT 101, (-)-gossypol; BAF, bafilomycin A1 ; BAK1, BCL2-antagonist/killer 1; BAX, BCL2-associated X protein; BH3, BCL2 homology region 3; BNIP3, BCL2 interacting protein 3; BNIP3L, BCL2 interacting protein 3 like; BP, Biological Process; CCCP, carbonyl cyanide m-chlorophenyl hydrazone; CC, Cellular Component; Con, control; CQ, chloroquine; CRISPR, clustered regularly interspaced short palindromic repeats; DMEM, Dulbecco's Modified Eagle Medium; DTT, 1, 4-dithiothreitol; EM, electron microscopy; ER, endoplasmatic reticulum; FACS, fluorescence-activated cell sorting; FBS, fetal bovine serum; FCCP, carbonyl cyanide 4-(trifluoromethoxy)phenylhydrazone; GO, Gene Ontology; HAcO, acetic acid; HMOX1, heme oxygenase 1; DKO, double knockout; LC-MS/MS, liquid chromatography coupled to tandem mass spectrometry; LPL, lipoprotein lipase, MEFs, mouse embryonic fibroblasts; mPTP, mitochondrial permeability transition pore; MTG, MitoTracker Green FM; mt-mKeima, mito-mKeima; MT-ND1, mitochondrially encoded NADH:ubiquinone oxidoreductase core subunit 1; PBS, phosphate-buffered saline; PE, phosphatidylethanolamine; PI, propidium iodide; PRKN, parkin RBR E3 ubiquitin protein ligase; SDS, sodium dodecyl sulfate; SQSTM1/p62, sequestome 1; STS, staurosporine; sgRNA, single guide RNA; SILAC, stable isotope labeling with amino acids in cell culture; TFA, trifluoroacetic acid, TMRM, tetramethylrhodamine methyl ester perchlorate; WM, wortmannin; WT, wild-type